Potency of anti-fibrotic herbs on fibrogenesis: A theoretical evaluation - Ramya Ramadoss; Sruthy Sathish; Honglae Sohn; Thirumurthy Madhavan (Elsevier, 2023)
Background: Fibrosis is characterized by excessive accumulation of extracellular matrix components within organs and tissues. Anti-fibrotic treatment represents an unconquered area for drug development, with enormous potential. Herbal concoctions provide an interesting pool of potential modulators of this disease process. Methods: In silico modeling of profibrotic genes using potential phytochemical agents will enable the identification of newer therapeutic agents. To virtually assess the efficacy of various phytochemicals as inhibitors of transforming growth factor-β (TGF-β) receptor and its downstream molecule SMAD using in silico methods, in comparison to the commercially available anti-fibrotic drug, Pirfenidone. A total of 4 phytochemicals were identified which showed stronger or similar binding affinity to TGF-β receptor type 2 molecule and SMAD molecule when compared to Pirfenidone, signifying their therapeutic potential. Results: Our study confirmed that plumbagin and ferulic acid can be used to target TGF; rhein and curcumin can be used to target SMAD and they have anti-fibrotic potential. Conclusions: The phytocompounds identified could be used as an anti-fibrotic drug in the treatment of fibrotic disorders. Furthermore, invitro and invivo experiments are to be carried out to validate the anti-fibrotic activity of these molecules.